Befintlig och framtida infrastruktur i Dennewitz malmkropp : Prognos och rekommendationer - Winsa, Johan (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2020)
During mining in the Malmberget mine, large amounts of information such as damage mapping, geological mapping, seismic data and stress conditions are stored. All the data that is obtained is stored in several places with different methods, which makes it problematic to use. The purpose of this work has been to compile, structure and interpret the collected data that is currently available. The aim of the compilation has been to use this information as a basis for what influence geology, structures, damage mapping and rock quality together have on the area around Dennewitz ore body. The ore in Dennewitz consists exclusively of magnetite and the surrounding rock is characterized by hard rock in form of leptites and granite, but also the soft mineral biotite. Leptites are the predominant rock types in the area, while granite appears in lenses at the deeper levels. Historically, granite and red leptite have been the rocks that have caused the most problems in the form of rock bursts. The Dennewitz hanging wall consists of grey leptite while the foot wall is dominated by red and red-grey leptite with minor areas of granite, and in a few places also biotite. The data compilation shows that there are flaws in the method for damage mapping, as the amount of useful data is very small compared to other areas. The compiled data on damage mapping shows that the majority of the damages is located along a large-scale geological structure that strikes in the same direction as the crosscuts. Damages are also located in the ore contact where granite and biotite lenses. The mapped damages with coordinates were used to obtain a limit angle. Using the damage coordinates, a plane representing the damages were created. The plane dips 60˚, which thus represents the limit angle for the damage zone. The plane has the same dip as the ore body and strikes 70˚ from the north over the crosscuts, and in some cases also the local ramp. Geologically, the drifts that runs along the orebody are the most problematic in the area. The contact ...